2022
DOI: 10.1155/2022/5699275
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-613 Enhances Nasopharyngeal Carcinoma Cell Radiosensitivity via the DNA Methyltransferase 3B/Tissue Inhibitor of Matrix Metalloproteinase-3/Signal Transducer and Activator of Transcription-1/Forkhead Box O-1 Axis

Abstract: Nasopharyngeal carcinoma (NPC) is a common malignancy of the nasopharynx, and radioresistant represents the main obstacle in NPC treatment. Malignant transformation of normal cells is driven by genetic and epigenetic changes, which are primarily manifested as changes in miRNA levels and DNA methylation status. microRNA (miR)-613 plays an inhibitory role in several types of cancer. Herein, the current study sought to explore the roles of miR-613 in NPC cell radiosensitivity. miR-613 expression patterns in NPC t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Research has shown a trend toward the expression of approximately fifty new miRNAs, such as miR-150, miR-483-5p and miR-454-3p, in radiation-resistant NPC ( 19 , 32 , 33 ). Furthermore, more than thirty miRNAs, including miR-31-5p, miR-613 and miR-340-3p, have been shown to modulate the radiosensitivity of NPC ( 34 36 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown a trend toward the expression of approximately fifty new miRNAs, such as miR-150, miR-483-5p and miR-454-3p, in radiation-resistant NPC ( 19 , 32 , 33 ). Furthermore, more than thirty miRNAs, including miR-31-5p, miR-613 and miR-340-3p, have been shown to modulate the radiosensitivity of NPC ( 34 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…demonstrated that miR-613 can decrease TIMP3 methylation and improve the expression of TIMP3 proteins by suppressing DNMT3B. As a result, the STAT1/FOXO1 signaling pathway was suppressed, and NPC cell sensitivity to radiation was enhanced ( 36 ). Notably, miR-124, which targets JAMA, can suppress stemness and increase NPC cells sensitivity to radiation both in vivo and in vitro ( 76 ).…”
Section: Resultsmentioning
confidence: 99%
“…Deng et al found that miR-613 enhances the radiosensitivity of NPC cells by inhibiting the downstream signal transducer and activator of transcription 1 (STAT1)/FOXO1 pathway 33 . In our study, western blotting results showed that FOXO1 levels were markedly decreased in NPC cells after HOXB2 overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…The authors observed that FOXO1 not only controlled tumor stemness and metastasis, but also sensitized NPC cells to cisplatin in vitro and in vivo [32] . Deng et al found that miR-613 enhances the radiosensitivity of NPC cells by inhibiting the downstream signal transducer and activator of transcription 1 (STAT1)/FOXO1 pathway [33] . In our study, western blotting results showed that FOXO1 levels were markedly decreased in NPC cells after HOXB2 overexpression.…”
Section: Discussionmentioning
confidence: 99%